PENGARUH KARAKTERISTIK KOMITE AUDIT DAN AUDITOR EKSTERNAL TERHADAP PENGUNGKAPAN MODAL INTELEKTUAL - Prameswari, Fanniya Dyah; Sudarno, Sudarno (Diponegoro Journal of Accounting, 2014)
This study is aimed to investigate the relationship between the characteristics of the audit committee and external auditors on the disclosure of intellectual capital. Intellectual capital disclosure (ICDI) variable is measured by using the 61 checklists in 3 formats namely tables, images and numeric. The populations in this study are the companies that are listed on the Indonesia Stock Exchange (IDX) in 2012. Total research sample is 100 companies that are selected by proportionate stratified random sampling method. This research analyzes the company's annual report using the method of content analysis. Data analysis is tested by the test of classical assumptions, test of hypothesis, and multiple linear regression analysismethod.The results of this research indicate that frequency meeting of audit committee are positively significant effect on intellectual capital disclosure.While, the financial expertise of the audit committee, the external auditor’ specialization and the quality of external auditors have no significant on intellectual capital disclosure.